Bróderes in arms: Gangs and the socialization of violence in Nicaragua. (September 2017) - Rodgers, Dennis
Drawing on longitudinal ethnographic research that has been ongoing since 1996, this article explores the way that gangs socialize individuals into violent norms and practices in Nicaragua. It shows how different types of gang violence can be related to distinct socialization processes and mechanisms, tracing how these dynamically articulate individual agency, group dynamics and contextual circumstances, albeit in ways that change over time. As such, the article highlights how gang socialization is not only a variable multilayered process, but also a very volatile one, which suggests that the socialization of violence and its consequences are not necessarily enduring.